PENGARUH KUALITAS PELAYANAN ROOM ATTENDANT TERHADAP KEPUASAN TAMU DI HOTEL SINTESA PENINSULA MANADO - Nathalia Chrisma Sigarlaki; Agustinus Walansendouw; Maxy Sondakh (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2022)
This study intention is to know the effect of room attendant service quality on guest statisfaction at Sintesa Peninsula Hotel Manado. The method used in this study is quantitive method using a simple linear regression model. The population on this study were the guest who come to stay at the Sintesa Peninsula Hotel Manado. Sample taken were 60 respondents. The data collected using questionaire. The result of this study using simple linear regression analysis at follow Y=20.666 + 0.265x showed a positive effect on the independent variable (Service Quality). Where if independent variabel increase then the guest statisfaction variable will also increase. From the analysis result correlation coefficient is found a value of 0,581 which showed that the two variable X and Y have a strong relationship where the significance value is 0,000 less than 0,05. furthermore, in the termination coefficient is it found that RSquare 0,338 means that the effect of the independent variable (Service Quality) on the dependent variable (Guest Statisfaction) os 33,8% and the remaining 66,2% is the influence of other variable that not elaborated in this study.